IMPLEMENTASI KEBIJAKAN PUBLIK SERTA TERHADAP KEPENTINGAN PUBLIK BERDASARKAN TEORI ADMINISTRASI NEGARA SAAT INI - Titi rawati Gulo; Rosalia Mendrofa; Elazhari (LPPM Universitas Cipta Mandiri, 2024)
Beyond the boundaries of the village's internal locality, village autonomy contains the principle of freedom to self-regulate, having its own customary law, and local resource capabilities or capacities. The integration of local resource freedom and capacity will give birth to village independence, namely in government affairs, making decisions. , and manage various resources in accordance with the preferences desired by the village community. Independence is the strength or improvement in the quality of village government administration, village development, development of local initiatives and potential, public services and the quality of life of village communities in a sustainable manner. The suggestion is that additional personnel are needed, especially for library management so that technical needs are not carried out by class teachers who already have the main task. Apart from that, it is necessary to develop programs to prevent boredom among students and it is also recommended to carry out evaluations on programs that are already running so that the effectiveness of a program can be seen for certain purposes.